Integrated metabolomics and transcriptomics reveal the role of calcium sugar alcohol in the regulation of phenolic acid biosynthesis in Torreya grandis nuts - Qiandan Xie; Zhengchu Jiang; Chenliang Yu; Qi Wang; Wensheng Dai; Jiasheng Wu; Weiwu Yu (BMC Plant Biology)
Abstract Background Torreya grandis, a prominent tree species of the autochthonous subtropical region of China, possesses a drupe-like fruit containing a nut that is rich in nutrients and bioactive compounds. However, the effect of calcium (Ca2+) sugar alcohol (CSA), a newly developed chelated Ca2+-fertilizer, on the secondary metabolism of phenolics in T. grandis nuts is largely unknown, for which transcriptomic and metabolomic analysis was carried out. Results Transcriptome sequencing detected 47,064 transcripts, and several phenolic acid biosynthesis pathway-related genes were identified. Correlation analysis showed that the four transcription factors, TgWRKY1, TgAP2-1, TgAP2-3, and TgAP2-4, were positively associated with the accumulation of phenolic acids. Furthermore, the binding of TgAP2-1 to the TgHCT promoter was confirmed using yeast one hybrid and dual-luciferase assays. Furthermore, the expression of TgHCT in Nicotiana enhanced the total flavonoid content. Conclusions Our results indicated that a new regulatory module, Ca2+–AP2–HCT, involved in the regulation of phenolic acid biosynthesis was revealed, expanding the understanding of the role of Ca2+ fertilizers in plant secondary metabolism.